Pengembangan Materi Ajar Teks Fabel Berbasis Video Animasi Berbantuan Aplikasi KineMaster Pro Pada Siswa Kelas VII SMP Swasta YPK Medan Tahun Ajaran 2022/2023 - Alfrija Irza Sahara; M. Joharis Lubis (Departement of Mathematics Education, 2024)
This study aims to describe the process of developing fable text teaching materials based on animated video assisted by the KineMaster Pro application, describe the product form of animated video based fable text teaching materials assisted by the KineMaster Pro application, and analyze the feasibility of fable text teaching materials based on animated videos assisted by the KineMaster Pro application. The development model used in this study is the Borg and Gall model which has ten steps but was modified by researchers into five steps namely, potential and problem, data collection, product design, design validation, and product revision. The research subjects used were 38 class VII students at SMP Swasta YPK Medan. While the object of his research is fable text material based on animated videos assisted by the KineMaster Pro application. Researchers used data collection techniques by interviewing techers and giving questionnaires in the form of questionnaires to students. The research instruments is in the form of a validation questionnaire sheet for material experts and media experts calculated using a likert scale. Data analysis used quantitative and qualitative. The results showed that the product of teaching materials for fable text based on video animation assisted by the KineMaster Pro application obtained a value of 85% from material experts in the “very good” category. While the results of media experts validation obtained a value of 90% in the “very good” category. So it can be stated that the product is very feasible to use.